Consumers Decision and Preference of Dry Sliced Arecas in Border Area (A Case Study in North Central Timor Regency) - Yoseph Daniel Jemai; Boanerges Sipayung; Umbu Joka; Dudi Septiadi (Junal Ilmu Manajemen, 2022)
People in North Central Timor Regency used the areca as their customary symbol and a pivotal part of their daily social life. This study aims to describe the factors affecting people's decision and preference to consume dry sliced areca nut sold in the market near the North Central Timor border. The population of this study was 259.000 people in the north-central Timor regency. As many as 360 people were recruited as the study samples using Isaac Michael's table with 10% margin of error. The study was conducted between December 2021 and February 2022. The collected data were analyzed using qualitative descriptive and logistic regression analysis techniques. This study found that age, gender, psychological factor, taste, and texture simultaneously affect consumers' decision in consuming dry sliced areca nuts. Age and texture were found to significantly affect the consumers' decisions in the North Central Timor Regency. Meanwhile, the texture was found to affect consumers' preference in selecting the dry sliced areca nut.